Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/clc.23154
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of familial hypercholesterolemia in patients with premature myocardial infarction

Abstract: Background Familial hypercholesterolemia (FH) is a genetic cause of premature myocardial infarction (PMI). Early diagnosis of FH is critical for prognosis. Hypothesis To investigate the prevalence of FH among a cohort of Chinese patients with PMI using genetic testing, and to evaluate different diagnostic criteria. Methods A total of 225 consecutive PMI patients were recruited. Low‐density lipoprotein receptor (LDLR), apolipoprotein B (APOB),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 30 publications
3
15
0
1
Order By: Relevance
“…A previous study carried out by the author of this study showed that the prevalence of FH diagnosed by genetic testing was 4.4% [7]. However, it was also found that not all clinical phenotypes of PMI matched gene mutations.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…A previous study carried out by the author of this study showed that the prevalence of FH diagnosed by genetic testing was 4.4% [7]. However, it was also found that not all clinical phenotypes of PMI matched gene mutations.…”
Section: Introductionmentioning
confidence: 63%
“…Data of PMI patients were retrieved from previously published studies to assess the clinical characteristics of PMI [7]. The clinical characteristics of non-PMI patients, including age, sex, body mass index (BMI), and family history of premature coronary heart disease (CHD), were collected via their medical records.…”
Section: Methodsmentioning
confidence: 99%
“…ethnicity, geography, etc. ), thus rendering clinical diagnostic criteria unsuitable in some populations of FH variant carriers [42]. In fact, racial disparities in age of FH diagnosis have been reported among those registered within the International FH Foundation's CASCADE Registry [43].…”
Section: Discussionmentioning
confidence: 99%
“…63 Averna et al [60] Jones et al [27] None reported 86. 33 Sperlongano et al [30] Amor-Salamanca et al [31] Minicocci et al [61] Séguro et al [62] Abul-Husn et al [21] Wang et al [63] Truong et al [34] Tan et al [35] Gómez et al [64] Cui et al [42] Ibarretxe et al [37] Chan et al [38] Cao et al [65]…”
Section: Discussionmentioning
confidence: 99%
“…Quando apresentada em heterozigose as variantes deste gene também apresentam fenótipo mais grave, tendo valores de LDL-c mais elevados que os demais. Há também uma variação do fenótipo de acordo com o tipo de variante identificada (ABUL-HUSN et al, 2016;CUI et al, 2019;SANTOS et al, 2014).…”
Section: Estudos Iniciais Do Nosso Grupo Relataram a Influência De Pounclassified